EXPERIENCES AND CHALLENGES IMPLEMENTING MASTER'S DEGREE PROGRAMMES IN MANAGEMENT - T. D. Maslova; M. V. Chigir (Дискурс)
This article analyzes the experience of Masters training in Management with the emphasis on contemporary factors influencing the process of Masters training, the problems whose solution depends on educational institutions are marked out, implements training programs for Masters. The survey data of Masters on usefulness of overseas internship during training at MA course and solutions of the revealed problems in Master's training in management are given.